Aku dalam Kehinaanku!: Menafsir Kehinaan Menurut Julia Kristeva - Paulus Eko Kristianto (Faculty of Theology Duta Wacana Christian University, 2017)
Abstract Abjection normally is understood as the gross taste. However, whether such humiliation is also understood when placed in the frame of philosophy? Julia Kristeva states abjection with regard to aesthetics in art and literature through poetry catharsis. That is through abjection, people are invited to immerse themselves further in selfhood. The key phrase is trying held by the author in this article outlines. The author tries to offer an alternative that has been wrapped Kristeva debasement in the language of the interface between semiotics and symbolism. Abstrak Kehinaan (abjection) biasa dipahami sebagai rasa jorok. Namun, apakah kehinaan juga dipahami demikian bila diletakkan dalam bingkai filsafat? Julia Kristeva menyatakan kehinaan berkaitan dengan estetika hina dalam seni dan sastra melalui katarsis puisi. Artinya, melalui kehinaan, manusia diajak untuk semakin membenamkan diri dalam kediriannya. Ungkapan kunci ini mencoba dipegang penulis dalam menguraikan artikel ini. Penulis mencoba menawarkan alternatif bahwa kehinaan telah dibalut Kristeva dalam bahasa persinggungan antara semiotika dan simbolisme.